Uji Total Coliform Pada Es Krim Yang Dijual Di Pasar Malam Wilayah Sungai Keledang - Lamri Lamri; Dita Irianti; Fadilahfani Rahmasari (CV. Wadah Publikasi Cendekia, 2023)
Ice cream is a frozen food product made with a combination of freezing processes on a mixture of ingredients consisting of milk, sweetener or sugar, stabilizer and emulsifier. Many factors can contaminate ice cream starting from raw materials, manufacturing methods, serving, equipment and so on. This study aims to determine the presence of coliform bacteria in ice cream sold at the night market in the keledang river area.This research is descriptive and was conducted at the Medical Bacteriology Laboratory in December 2021 - July 2022. The samples used were ice cream sold at the night market as many as 7 samples of the Keledang River Area. Sampling technique using total sampling technique with univariate data analysis. This research uses primary data from the results of the examination using the Most Probable Number (MPN) method.Based on the results obtained in the study, it is known that 7 ice cream samples examined were contaminated with coliform bacteria with values of 2.2, 4.4, 5, 7.5, 7.5, 12 and 17 MPN/100mL samples. This shows that 1 sample in S6 is eligible and 6 samples are not eligible in S1, S2, S3, S4, S5 and S7. The safe limit of coliform bacteria contamination set by BPOM RI Number HK 00/06/1/52/401/2009 that the MPN Coliform value is 3/100ml sample. Keywords: Coliform Bacteria, Ice Cream, Most Probable Number (MPN)